Responsible Branding in Asia: Are Companies Ready? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
Jorg Dietzel was born in Germany in 1961. An advertising industry veteran, he opened his own brand consultancy, Jorg Dietzel Brand Consultants, in Singapore two years ago, and teaches classes on Advertising and Strategic Brand Management at Singapore Management University's Lee Kong Chian School of Business. Dietzel talks to Knowledge@SMU about why companies in Asia need to re-brand themselves as responsible corporate citizens or face losing out to competitors.